Tecnologias de informação e comunicação: percepção dos profissionais de saúde e educação sobre sua utilização para acesso à informação sobre o crack - Novais, Maykon Anderson Pires de [UNIFESP] (2016)
Introduction: Crack, a cocaine derivative, is considered a devastating drug due to its physical, psychological and social effects. Initially restricted to the city of São Paulo, with great penetration in the lower social classes, is currently disrupting social and geographical barriers, being present in all Brazilian cities. It has become a major challenge, especially for professionals working in prevention of use, such as teachers and those involved in users? treatment, such as health professionals. Quick access to right information is one of the most efficient ways for these professionals to combat the drug and its consequences. Objectives: To identify the information and communication technologies used by health and education professionals to assist in training and updating of technical and scientific knowledge about crack, exchange of experiences and development of programs to prevent consumption and treatment of addicts. Also, to examine the access to information deficiencies observed by the investigated professionals. Methodology: The objective was reached from the interviewees. It used a qualitative methodology that allows the understanding of the phenomenon from the point of view of one who experiences it. Purposive sample by criteria was built and techniques of qualitative research were used: semi-structured interviews, triangulation analysis and key informants. Results: The study resulted in the presentation of differences between the way key informants and education and health professionals sought information. In both cases internet was the preferred source, however key informants sought information on sites of scientific journals and reference centers, while education and health professionals did free searches on the internet to consume information. Discussion: The literature does not reflect a broad scope of the specific area, but relates the problem of access to health information to other characteristics, which compromises the professional training, expanding the performance spectrum of quality health and education professionals. The data, when analyzed and compared, presented a very fertile panorama for training health and education professionals, especially as it compares to the reference professionals (key informants). Conclusion: The scope of the study concluded that the sources of information about crack are diverse, but focused on digital technologies, especially the internet and its specific tools. It also finds that health and education professionals are not trained solidly on the subject of study.